The synthesis and characterization of aryloxy-linear phosphazenes - Çil, E; Arslan, M; Aslan, F; Öztürk, AI (Taylor & Francis Ltd, 2003)
The reactions of N-dichlorophosphoryl-P-trichloromonophosphazene with sodium o-methylphenoxide, sodium p-methylphenoxide, sodium alpha-naphthalenoxide, monosodium 4-(2-pyridylazo)resorcinol, and sodium 1-nitroso-2-naphthaleneoxide have been investigated. Experimental studies were carried out in argon atmosphere. The sodium aryloxides were prepared from naphthalene or phenol derivatives and metallic sodium. The phosphazene and phenolate or naphthaleneoxide were reacted at 0degreesC and then refluxed. After the reaction products were separated by using column chromatography, the structures of the compounds were defined by elemental analysis, IR, H-1, C-13, (PNMR)-P-31, and mass spectroscopy. Tetra- and pentasubstituted monophosphazenes were obtained from sodium o-methylphenoxide. Pentasubstituted derivatives also were obtained from sodium p-methylphenoxide and sodium alpha-naphthaleneoxide. Phosphazene or any phosphorus compound could not be isolated from the reaction of phosphazene with monosodium 4(2-pyridylazo)resorcinol and sodium 1-nitroso-2-naphthaleneoxide.
Keywords: linear phosphazenes; N-dichlorophosphoryl-P-trichloromonophosphazene; phenolysis of acyclic monophosphazene